Intermodal Integration Analysis at Manggarai Central Station - Khoeruddin Yogi Pratama; Herwin Siregar; Kasimir Sawito (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to assess the level of safety, comfort and efficiency between various modes of transportation and the criteria for assessing are integration of payment systems, suitability of schedules, transit facilities, and completeness of information. Each criterion is identified, where these criteria can be measured quantitatively through primary and secondary data collection. In this study, an evaluation of the integration of KRL Commuter line, Airport Train and Transjakarta was carried out which is located at Manggarai Central Station. In this study, the Analytical Hierarchy Process (AHP) method was used to evaluate 4 criteria, with the calculation results showing the order of assessment criteria starting from the highest, namely the payment system with a value of 0.434285562, transit facilities with a value of 0.262313003, schedule suitability with a value of 0, 165718117 and completeness of information with a value of 0.156162323. Based on the results of this assessment, the KRL Commuter line integration service with the Airport and Transjakarta Trains at Manggarai Central Station can be used as a reference for other stations to achieve minimum service standards for intermodal integration.